Economic reforms in India and China : emerging issues and challenges - Sudhakara Reddy, B. (SAGE Publications India ; SAGE, 2009)
Papers presented at a conference held at Mumbai in February 2005.
Keywords: India -- Economic conditions -- 1991-; India -- Economic policy -- 1991-2016.; China -- Economic conditions -- 2000-; China -- Economic policy -- 2000-; Inde -- Conditions économiques -- 1991-; Inde -- Politique économique -- 1991-2016.; Chine -- Conditions économiques -- 2000-; Chine -- Politique économique -- 2000-; POLITICAL SCIENCE -- Economic Conditions.; BUSINESS & ECONOMICS -- Economics -- Comparative.; BUSINESS & ECONOMICS -- Economic Conditions.; BUSINESS & ECONOMICS -- Economic History.; Economic history; Economic policy; China; India; Wirtschaftsreform; Indien; Wirtschaftsreform.; Fiskalische Dezentralisierung.; Direktinvestition.; Finanzsektor.; Agraraußenhandel.; Indien.; China.; Since 1991